Legal and Social Implications of Cryptocurrency Adoption in Developing Countries - Meiske Mariana Wenseslas Lasut; Engeli Yuliana Lumaing; Ademsi Timomor; Wenly R. J. Lolong; Reynold Simanjuntak (Technium Social Sciences Journal, 2024)
This study aims to analyze the legal and social implications of cryptocurrency adoption in developing countries. This study adopts a holistic approach that integrates legal, social, and economic analysis to provide a more comprehensive understanding. This study uses a qualitative method with a literature review approach. Data were collected through a systematic search of academic databases using relevant keywords. Thematic analysis was conducted to identify key themes related to cryptocurrency adoption in developing countries. Triangulation of data sources and consideration of geographical context were conducted to ensure the validity of the results. The results show that cryptocurrency adoption in developing countries has significant potential but also presents complex challenges. Some of the key findings include: cryptocurrency has the potential to increase financial inclusion for the unbanked population; developing countries face regulatory dilemmas in adopting cryptocurrency; widespread adoption of cryptocurrency can affect macroeconomic stability; cryptocurrency shows the potential to revolutionize the remittance sector; limited technological infrastructure is a major barrier to adoption; cryptocurrency adoption has diverse social implications, including the risk of widening the digital divide; lack of consumer protection mechanisms is a major concern; international collaboration is essential in addressing adoption challenges; low financial and digital literacy are significant barriers; and cryptocurrency adoption raises environmental concerns related to energy use.